#### Answer

$= \frac{(t+5)}{(t-6)}$

#### Work Step by Step

$\frac{t^{2}+2t-15}{t^{2}-9t+18}$
$= \frac{t^{2}+5t-3t-15}{t^{2}-6t-3t+18}$
$= \frac{t(t+5)-3(t+5)}{t(t-6)-3(t-6)}$
$= \frac{(t-3)(t+5)}{(t-3)(t-6)}$
$= \frac{(t+5)}{(t-6)}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$= \frac{(t+5)}{(t-6)}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.